Effectiveness of Constructivism Theory of Learning as 21st Century Method of Teaching - Daodu, M; Elegbede, C; Adedotun, O (Journal of Advanced Psychology, 2024)
The paper introduced the concept of constructivism theory of learning as an effective method of teaching in 21st century. Adequate effort was made to vividly explain the meaning, two major types and principles of constructivism learning theory. Likewise, the paper examined the role and characteristics of the usage of constructivism theory as a teaching method. The nature, setting and characteristics of constructivism classroom were also discussed. Benefits to be derived when constructivism theory is used as a teaching method is explicitly explained. Few criticisms raised against the use of this theory as teaching method were expatiated and resolve. The study recommends that effective usage of this method would certainly enhance learning mastery and ownership knowledge by the learners.